6(3y-1)+2-(-3+4)=

Simple and best practice solution for 6(3y-1)+2-(-3+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3y-1)+2-(-3+4)= equation:


Simplifying
6(3y + -1) + 2 + -1(-3 + 4) = 0

Reorder the terms:
6(-1 + 3y) + 2 + -1(-3 + 4) = 0
(-1 * 6 + 3y * 6) + 2 + -1(-3 + 4) = 0
(-6 + 18y) + 2 + -1(-3 + 4) = 0

Combine like terms: -3 + 4 = 1
-6 + 18y + 2 + -1(1) = 0

Multiply -1 * 1
-6 + 18y + 2 + -1 = 0

Reorder the terms:
-6 + 2 + -1 + 18y = 0

Combine like terms: -6 + 2 = -4
-4 + -1 + 18y = 0

Combine like terms: -4 + -1 = -5
-5 + 18y = 0

Solving
-5 + 18y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 18y = 0 + 5

Combine like terms: -5 + 5 = 0
0 + 18y = 0 + 5
18y = 0 + 5

Combine like terms: 0 + 5 = 5
18y = 5

Divide each side by '18'.
y = 0.2777777778

Simplifying
y = 0.2777777778

See similar equations:

| 6m-5=-5m+7 | | 9+4t=6 | | 2x-(5x-7)-x=2(x+2)-8 | | 3x^2+18x+3=6 | | -5s^2+5s+9=0 | | 97+80+70+88+s=375 | | 5t-8=9t-10 | | 9=-6p+3/-8 | | -5a+16+3a=8a-6a | | 9-2x/7=5 | | a/2-10=a+20 | | 6x+2=16-x | | 9=-6+3/-8 | | 2(4-d)-5d=8 | | .4(x+70)+1.2x=92 | | -2r^2-9r-5=0 | | X/7+5=-5 | | 5x+1=8-2x | | 2/5x+4=12 | | 11=7+x^6 | | 6u^2+9u+3=0 | | 3x(x-2)-1=3(x+2)(x+4) | | -3=-5-2y | | (b+2)x(b-3)= | | -8y-3=7y-6 | | 17-(4x-6)=58 | | 0=r-16 | | 9k^2+9k+1=0 | | 1/4(9+2x)=19 | | -1=-x/4-6 | | 6(x-1)+8=4x+2(-1+x) | | 9n^2+4n=0 |

Equations solver categories